Twenty thousand fleas under the sea - Pilkey, Dav, 1966-; Garibaldi, Jose; Dzioba, Wes; Beard, George (Fictitious character); Hutchins, Harold (Fictitious character) (2023)
Piggy is back, and his newest plot is his most diabolical yet. Dog Man and the rest of your favorite characters must join together. What new villains are on the horizon? Where are they all coming from? And who will step forward to save the city when scoundrels sabotage our Supa Buddies?
Includes bibliographical references.
007-009.
Keywords: Dog Man -- (Fictitious character) -- Comic books, strips, etc; Dog Man -- (Fictitious character) -- Juvenile fiction; Dogs -- Comic books, strips, etc; Cats -- Comic books, strips, etc; Police -- Comic books, strips, etc; Dogs -- Juvenile fiction; Cats -- Juvenile fiction; Police -- Juvenile fiction